To add the given expressions using the properties of operations, we'll first distribute the coefficients:
9(k + 1/3) + 10(1/2k - 1)
= 9k + 9(1/3) + 10(1/2k) - 10(1)
= 9k + 3 + 5k - 10
Next, combine like terms:
= (9k + 5k) + (3 - 10)
= 14k - 7
So, the simplified expression is 14k - 7.
use the properties of operations to add 9 (k+ 1/3)+10 (1/2 k-1)
10 answers
use the properties of operations to add 4 (g-2)+(g+2)
To add the given expressions using the properties of operations, we will first distribute the coefficients:
4(g - 2) + (g + 2)
= 4g - 8 + g + 2
Next, combine like terms:
= (4g + g) + (-8 + 2)
= 5g - 6
So, the simplified expression is 5g - 6.
4(g - 2) + (g + 2)
= 4g - 8 + g + 2
Next, combine like terms:
= (4g + g) + (-8 + 2)
= 5g - 6
So, the simplified expression is 5g - 6.
use the properties of operations to add (h+k) - (2k-h)
To add the given expressions using the properties of operations, we'll first distribute the negative sign in front of the second expression:
(h + k) - (2k - h)
= h + k - 2k + h
Next, combine like terms:
= (h + h) + (k - 2k)
= 2h - k
So, the simplified expression is 2h - k.
(h + k) - (2k - h)
= h + k - 2k + h
Next, combine like terms:
= (h + h) + (k - 2k)
= 2h - k
So, the simplified expression is 2h - k.
use the properties of operations to subtract (p-3) - (2.4+2p)
To subtract the given expressions using the properties of operations, we'll distribute the negative sign to both terms within the parentheses, -1(2.4 + 2p), which gives us:
(p - 3) - (2.4 + 2p)
= p - 3 - 2.4 - 2p
Next, combine like terms:
= (p - 2p) + (-3 - 2.4)
= -p - 5.4
So, the simplified expression is -p - 5.4.
(p - 3) - (2.4 + 2p)
= p - 3 - 2.4 - 2p
Next, combine like terms:
= (p - 2p) + (-3 - 2.4)
= -p - 5.4
So, the simplified expression is -p - 5.4.
subtract 2(k-4)-3(2k-1)
To subtract the given expressions, we'll distribute the coefficients:
2(k - 4) - 3(2k - 1)
= 2k - 8 - 6k + 3
Next, combine like terms:
= (2k - 6k) + (-8 + 3)
= -4k - 5
So, the simplified expression is -4k - 5.
2(k - 4) - 3(2k - 1)
= 2k - 8 - 6k + 3
Next, combine like terms:
= (2k - 6k) + (-8 + 3)
= -4k - 5
So, the simplified expression is -4k - 5.
I got 100